Welche Tierwohlmaßnahmen sollten in einem Tierwohlprogramm umgesetzt werden? Eine Stakeholder-Analyse; Which Animal Welfare Measures should be implemented in Animal Welfare Programs? A Stakeholder Analysis - Heinke Heise; Ludwig Theuvsen (German Journal of Agricultural Economics (GJAE), 2017)
– In response to the growing number of citizens who express concerns about farm animal welfare in intensive, modern livestock farming, a number of programs that sell meat and other food products of animal origin from more animal friendly production systems (so called animal welfare programs) have emerged on the market in recent years. To successfully establish an animal welfare program in the market, the acceptance of several stakeholders along the supply chains of food products of animal origin is needed. For this reason, based on three quantitative empirical studies, this study investigates the perceived importance and practicability of 13 often discussed animal welfare measures from farmers', veterinarians' and consumers' point of view. The results show that the evaluations of the animal welfare measures surveyed differ widely between the stakeholder groups. However, the results also give evidence that it is not impossible to develop an animal welfare program which meets the common concerns of consumers regarding animal welfare and at the same time is accepted by the experts directly involved in livestock production. For some animal welfare measures, there is still research demand to improve the practicability in conventional livestock farming. This is particularly urgent for the provision of outdoor access and the renouncement of curative interventions such as tail docking or teeth clipping as consumers rate these animal welfare measures as important for the wellbeing of animals while, at the same time, conventional farmers rate their practicability rather low. From the results, first implications for the conception of animal welfare programs can be derived. Thus, our study can help to establish a broader market segment for products from more animal friendly production system. In this way the more and more critical discourse between the broader public and the agricultural sector can be mitigated.
Keywords: 330